UFOs: Myths, Conspiracies, and Realities by John B. Alexander - Randle, Kevin (Journal of Scientific Exploration, 2012)
It is said that the truest test of a man’s intelligence is how much he agrees with you, and I find that Dr. Alexander and I share a great number of opinions. I looked first at the chapter about Philip Corso, who claimed an inside knowledge of the Roswell UFO crash and the government plans to exploit the find by seeding recovered material into American industry. Here Alexander writes not only from his experience in the Pentagon and classified operations, but as a friend of Corso. He spoke with him in the weeks prior to Corso’s death. But Alexander found many holes in the stories spun by Corso, and in the end, while acknowledging Corso’s long military career, did not truly believe him. Here Alexander and I agree. What was more fascinating was Alexander’s discussion of Congressional hearings about UFOs, and what disclosure would accomplish. Writing as an insider who has experience in this arena, Alexander suggested that neither hearings nor disclosure was going to happen for reasons he carefully lays out.